(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2021)
The present work aims to develop a stable and optimized bilayer dosage form containing immediate release &extended release drug Nicardapine as an extended-release dosage form. A potent calcium channel blocker with marked vasodilator action. It has antihypertensive properties and is effective in the treatment of angina and coronary spasms without showing cardio depressant effects. It has also been used in the treatment of asthma and enhances the action of specific antineoplastic agents. It has a plasma half-life of about (8.6h) and bioavailability is 15-45% orally. For the formulation of Bilayered tablets polymers such as Ethylcellulose, Sodium CMC, CCS, SSG, Magnesium stearate, Talc, PVP-K30, and MCC. Fourier transform Infrared spectroscopy confirmed the absence of any drug/ polymers/ excipients interactions. Preformulation studies were carried out to optimize the ratios required for various Ethylcellulose, Sodium CMC, CCS, SSG, MCC, and PVP-K30. Based on various evaluation parameters formulation M6 (IR) & M6F3 (SR) were selected as optimized formulation. It was observed that Formulations M6 (IR) & M6F3 (SR) gave maximum drug release within time. All formulations were subjected for drug release kinetics studies viz. Zero-order, First order, Higuchi matrix, Peppasmodel equations, and the formulations of floating sustained-release formulations followed the zero-order release with non-fickian diffusion mechanism. Thus conclusion can be made that a stable dosage form can be developed for Nicardapine as immediate release & sustained release by Bilayered tablets.